In need of change: The scientific practice of representing business models - John, Thomas; Kundisch, Dennis (Proceedings of the 14th International Conference on Enterprise Information Systems)

Approaches for Business Model Representation: An Overview - Kundisch, Dennis; John, Thomas; Honnacker, Jörg; Meier, Christian (Proceedings of the Multikonferenz Wirtschaftsinformatik (MKWI))

Towards a Classification Framework for Business Model Representations - Kundisch, Dennis; John, Thomas; Honnacker, Jörg; Meier, Christian (6th International Workshop on Value Modeling and Business Ontology)

Business Model Representation Incorporating Real Options: An Extension of e3-value - Kundisch, Dennis; John, Thomas (Proceedings of the 45th Hawaii International Conference on System Sciences (HICSS))

Evidence-Based Guideline of the German Nutrition Society: Carbohydrate Intake and Prevention of Nutrition-Related Diseases - Hauner, Hans; Bechthold, Angela; Boeing, Heiner; Brönstrup, Anja; Buyken, Anette; Leschik-Bonnet, Eva; Linseisen, Jakob; Schulze, Matthias; Strohm, Daniela; Wolfram, Günther (Annals of Nutrition and Metabolism)

Is breastfeeding related to bone properties? A longitudinal analysis of associations between breastfeeding duration and pQCT parameters in children and adolescents - Kühn, Tilman; Kroke, Anja; Remer, Thomas; Schönau, Eckhard; Buyken, Anette (Maternal & Child Nutrition)

Prospective associations of dietary insulin demand, glycemic index, and glycemic load during puberty with body composition in young adulthood - Joslowski, G; Goletzke, J; Cheng, G; Günther, A L B; Bao, J; Brand-Miller, J C; Buyken, Anette (International Journal of Obesity)

Die DONALD Kohorte - Buyken, Anette; Alexy, U.; Kersting, M.; Remer, T. (Bundesgesundheitsblatt - Gesundheitsforschung - Gesundheitsschutz)

Increase in prevalence of adiposity between the ages of 7 and 11 years reflects lower remission rates during this period - von Kries, R.; Reulen, H.; Bayer, O.; Riedel, C.; Diethelm, K.; Buyken, Anette (Pediatric Obesity)

Kohlenhydratzufuhr und Prävention ausgewählter ernährungsmitbedingter Krankheiten - Hauner, H.; Bechthold, A.; Boeing, H.; Brönstrup, A.; Buyken, Anette; Leschik-Bonnet, E.; Linseisen, J.; Schulze, M.; Strohm, D.; Wolfram, G. (DMW - Deutsche Medizinische Wochenschrift)

Beyond overweight: nutrition as an important lifestyle factor influencing timing of puberty - Cheng, Guo; Buyken, Anette; Shi, Lijie; Karaolis-Danckert, Nadina; Kroke, Anja; Wudy, Stefan A; Degen, Gisela H; Remer, Thomas (Nutrition Reviews)

IT-Projektportfolios mit Projektabhängigkeiten wertorientiert gestalten - Zimmermann, Steffen; Heinrich, B.; Kundisch, Dennis (Organisation des IT-Projekt- und IT-Projektportfoliomanagements)

Algorithmic Trading - Honnacker, Jörg; Kundisch, Dennis (Banklexikon)

Ausserbörslicher Direkthandel - Herrmann, Philipp; Kundisch, Dennis (Banklexikon)

Online Broker / Online Brokerage - Mutter, Tobias; Kundisch, Dennis (Banklexikon)

Scientiﬁc Literature Retrieval based on Terminological Paraphrases using Predicate Argument Tuple - Choi, Sung-Pil; Song, Sa-kwang; Jung, Hanmin; Geierhos, Michaela; Myaeng, Sung Hyon (Information Science and Industrial Applications: Proceedings, International Conference, ISI 2012, Cebu, Philippines, May 2012)
The conceptual condensability of technical terms permits us to use them as effective queries to search scientific databases. However, authors often employ alternative expressions to represent the meanings of specific terms, in other words, Terminological Paraphrases (TPs) in the literature for certain reasons. In this paper, we propose an effective way to retrieve “de facto relevance documents” which only contain those TPs and cannot be searched by conventional models in an environment with only controlled vocabularies by adapting Predicate Argument Tuple (PAT). The experiment confirms that PAT-based document retrieval is an effective and promising method to search those kinds of documents and to improve terminology-based scientific information access models.

A Proof-of-Concept of D³ Record Mining using Domain-Dependent Data - Lee, Yeong Su; Geierhos, Michaela; Song, Sa-Kwang; Jung, Hanmin (Software Technology: Prooceedings, International Conference, SoftTech 2012, Cebu, Philippines, May 2012)
Our purpose is to perform data record extraction from onlineevent calendars exploiting sublanguage and domain characteristics. We therefore use so-called domain-dependent data (D³) completely based on language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Moreover, another important criteria is that our system is robust to DOM and layout modifications made by web designers. Thus, preliminary experimental results are provided to demonstrate proof-of-concept of such an approach tested on websites in the German opera domain. Furthermore, we could show that our proposed technique outperforms other data record mining applications run on event sites.

Customer Interaction Management goes Social: Getting Business Processes plugged in Social Networks - Geierhos, Michaela; Ebrahim, Mohamed (Computational Social Networks: Tools, Perspectives and Applications)
Within this chapter, we will describe a novel technical service dealing with the integration of social networking channels into existing business processes. Since many businesses are moving to online communities as a means of communicating directly with their customers, social media has to be explored as an additional communication channel between individuals and companies. While the English-speaking consumers on Facebook are more likely to respond to communication rather than to initiate communication with an organisation, some German companies already have regularly updated Facebook pages for customer service and support, e.g. Telekom. Therefore, the idea of classifying and evaluating public comments addressed to German companies is based on an existing demand. In order to maintain an active Facebook wall, the consumer posts have to be categorised and then automatically assigned to the corresponding business processes (e.g. the technical service, shipping, marketing, accounting, etc.). This service works like an issue tracking system sending e-mails to the corresponding person in charge of customer service and support. That way, business process management systems which are already used to e-mail communication can benefit from social media. This allows the company to follow general trends in customer opinions on the Internet; moreover it facilates the recording of two-sided communication for customer relationship management and the company’s response will be delivered through consumer’s preferred medium: Facebook.

FPGA-based design and implementation of an approximate polynomial matrix EVD algorithm - Kasap, Server; Redif, Soydan (Proc. Int. Conf. on Field Programmable Technology (ICFPT))

Semi-automatic establishment and maintenance of valid traceability in automotive development processes - Fockel, Markus; Holtmann, Jörg; Meyer, Jan (2012 Second International Workshop on Software Engineering for Embedded Systems (SEES))
The functionality realized by software in modern cars is increasing and as a result the development artifacts of automotive systems are getting more complex. The existence of traceability along these artifacts is essential, since it allows to monitor the product development from the initial requirements to the final code. However, traceability is established and maintained mostly manually, which is time-consuming and error-prone. A further crucial problem is the assurance of the validity of the trace links, that is, the linked elements are indeed related to each other. In this paper we present a semiautomatic approach to create, check, and update trace links between artifacts along an automotive development process.

ESB: Ext2 Split Block Device - Kaiser, Jürgen; Meister, Dirk; Hartung, Tim; Brinkmann, André (Proc. IEEE Int. Conf. on Parallel and Distributed Systems (ICPADS))

A Study on Data Deduplication in HPC Storage Systems - Meister, Dirk; Kaiser, Jürgen; Brinkmann, André; Kuhn, Michael; Kunkel, Julian; Cortes, Toni (Proc. Int. Conf. on Supercomputing (SC))

FPGA implementation of a second-order convolutive blind signal separation algorithm - Kasap, Server; Redif, Soydan (Int. Architecture and Engineering Symp. (ARCHENG))

Towards Dynamic Scripted pNFS Layouts - Grawinkel, Matthias; Süß, Tim; Best, Georg; Popov, Ivan; Brinkmann, André (Proc. Parallel Data Storage Workshop (PDSW))

A Single Sign-On Infrastructure for Science Gateways on a Use Case for Structural Bioinformatics - Gesing, Sandra; Grunzke, Richard; Krüger, Jens; Birkenheuer, Georg; Wewior, Martin; Schäfer, Patrick; Schuller, Bernd; Schuster, Johannes; Herres-Pawlis, Sonja; Breuers, Sebastian; Balaskó, Ákos; Kozlovszky, Miklos; et al. (Journal of Grid Computing)

Comparison of Bayesian Move Prediction Systems for Computer Go - Wistuba, Martin; Schaefers, Lars; Platzner, Marco (Proc. IEEE Conf. on Computational Intelligence and Games (CIG))

Generic User Management for Science Gateways via Virtual Organizations - Schlemmer, Tobias; Grunzke, Richard; Gesing, Sandra; Krüger, Jens; Birkenheuer, Georg; Müller-Pfefferkorn, Ralph; Kohlbacher, Oliver (Proc. EGI Technical Forum)

One Phase Commit: A Low Overhead Atomic Commitment Protocol for Scalable Metadata Services - Congiu, Giuseppe; Grawinkel, Matthias; Narasimhamurthy, Sai; Brinkmann, André (Proc. Workshop on Interfaces and Architectures for Scientific Data Storage (IASDS))

A Data Driven Science Gateway for Computational Workflows - Grunzke, Richard; Birkenheuer, Georg; Blunk, Dirk; Breuers, Sebastian; Brinkmann, André; Gesing, Sandra; Herres-Pawlis, Sonja; Kohlbacher, Oliver; Krüger, Jens; Kruse, Martin; Müller-Pfefferkorn, Ralph; Schäfer, Patrick; et al. (Proc. UNICORE Summit)

Experimentelle Untersuchung und Simulation des Crashverhaltens mechanisch gefügter Verbindungen - Hein, David; Meschut, Gerson; Hahn, Ortwin; Bier, Matthias; Harder, Wolfgang (2. Fügetechnisches Gemeinschaftskolloquium)

Charakterisierung und Modellierung des Bruchverhaltens von Punktschweißverbindungen in pressgehärteten Stählen - Hein, David; Meschut, Gerson; Hahn, Ortwin; Klokkers, Frederik (11. LS-DYNA Forum 2012)

On the Admission of Dependent Flows in Powerful Sensor Networks - Cohen, Reuven; Nudelman, Ilia; Polevoy, Gleb (Infocom'2012, Orlando, Florida)

Talking like a book. Investigating colloquialization as a change in written English - Mindt, Ilka (Oralité(s) et écriture(s))

Change in Contemporary English. A Grammatical Study - Mindt, Ilka; Leech, Geoffrey; Hundt, Marianne; Mair, Christian; Smith, Nicholas (Archiv für das Studium der neueren Sprachen und Literaturen 164: 249: 2)

Design of an exact data deduplication cluster - Kaiser, Jürgen; Meister, Dirk; Brinkmann, André; Effert, Sascha (Proc. Symp. on Mass Storage Systems and Technologies (MSST))

Editorial for Algorithmic Aspects of Wireless Sensor Networks - Dolev, Shlomi; Scheideler, Christian (Theor. Comput. Sci.)

Selfish Distributed Optimization - Monien, Burkhard; Scheideler, Christian (Euro-Par 2012 Parallel Processing - 18th International Conference, Euro-Par 2012, Rhodes Island, Greece, August 27-31, 2012. Proceedings)

Materielles und Immaterielles Kulturerbe - global, regional, glokal? - Seng, Eva- Maria (Vortrag auf der Tagung "Kulturerbe Baden-Württemberg" des Museumsverbandes Baden-Württemberg e.V., Stuttgart 09.-10.03.2012)

Eine gewinnbringende Kooperation zwischen Museum und Universität - Seng, Eva- Maria (Freilichtmagazin 2012. Mitteilungen aus dem LWL-Freilichtmuseum Detmold – Westfälisches Landesmuseum für Volkskunde H7)

Revisionen: Städtebau im 18. Jahrhundert - Seng, Eva- Maria; Gieser, Laura; Göttmann, Frank (Francia. Forschungen zur westeuropäischen Geschichte, Bd. 39)

Das Ende des Nachkriegsstädtebaus: Stadtumbau Ost - Stadtumbau West: neue Mitte Ulm und Potsdamer Mitte - Seng, Eva- Maria (Kunst und Architektur in Mitteldeutschland. Thomas Topfstedt zum 65. Geburtstag)

Utopie und Architektur - Seng, Eva- Maria; Saage, Richard (L’Architecture engagée. Manifeste zur Veränderung der Gesellschaft (Publikation zur Ausstellung des Architekturmuseums der TU München in der Pinakothek der Moderne 14. Juni bis 02. September 2012)

Deutschsprachige Literatur(en) seit 1989

Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben

Schemata und Praktiken

Deutschsprachige Literatur(en) seit 1989. Zur Einführung - Eke, Norbert Otto; Elit, Stefan (Zeitschrift für deutsche Philologie (Sonderheft "Deutschsprachige Literatur(en) seit 1989" zum Band 131))
Angaben zur Herausgeberschaft: Hg. von Norbert Otto Eke und Stefan Elit

Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben. Dreißig Jahre Paderborner Gastdozentur für Schriftstellerinnen und Schriftsteller - Eke, Norbert Otto (Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben)

Werner Fritsch: „Theater gegen alles Theater“ - Eke, Norbert Otto (Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben)

Lea Singer: Nähe in der Distanz – Humilitas und Emphase - Eke, Norbert Otto (Poetologisch-poetische Interventionen: Gegenwartsliteratur schreiben)

Beobachtungen beobachten. Beiläufiges aus germanistischer Sicht zum Umgang mit einer Literatur der Gegenwärtigkeit - Eke, Norbert Otto (Doing Contemporary Literature. Praktiken, Wertungen, Automatismen)